2010
DOI: 10.1016/j.ijrobp.2009.03.079
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose–Volume Effects in the Larynx and Pharynx

Abstract: The dose-volume-outcome data for RT-associated laryngeal edema, laryngeal dysfunction, and dysphagia, have only recently been addressed, and are summarized. For late dysphagia, a major issue is accurate definition and uncertainty of the relevant anatomical structures. These and other issues are discussed. Radiation therapy (RT) is the primary modality allowing larynx preservation in patients with tumors in the upper aero-digestive tract. RT-induced laryngeal edema (due to inflammation and lymphatic disruption)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(134 citation statements)
references
References 26 publications
6
124
1
3
Order By: Relevance
“…They were defined prior to commencement of the AP evaluation. The OAR score values are based on biological endpoints 20 , 21 , 22 , 23 and attempt to capture the physician's perception of the relative importance of different dose goals. Taking the parotid gland as an example, the maximum available score is 15, relative to the target coverage maximum score of 25.…”
Section: Methodsmentioning
confidence: 99%
“…They were defined prior to commencement of the AP evaluation. The OAR score values are based on biological endpoints 20 , 21 , 22 , 23 and attempt to capture the physician's perception of the relative importance of different dose goals. Taking the parotid gland as an example, the maximum available score is 15, relative to the target coverage maximum score of 25.…”
Section: Methodsmentioning
confidence: 99%
“…For the OARs, the population-averaged mean doses (AE standard deviation) and the maximal doses to the spinal cord and carotid arteries were reported. It has been recommended to keep the dose in the larynx less than $66 Gy for vocal function preservation (2). Therefore, the volume of the CL vocal cord that received $95% of the prescribed dose or more was also reported.…”
Section: Treatment Plansmentioning
confidence: 99%
“…One major area of concern for head and neck treatments is the dosimetric sparing of a patient's salivary glands, pharyngeal constrictors, and larynx. High doses of radiation to these organs can cause dry mouth (xerostomia) and difficulty swallowing (dysphagia) 2, 3, 4, 5, 6. Sparing a patient's salivary glands and larynx has been shown to reduce symptoms and increase patient quality of life 2, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…The QUANTEC review of dose–volume effects on salivary function by Deasy et al concluded that for IMRT plans the mean dose to each parotid gland should be kept as low as possible 3. It also states that, “a lower mean dose to the parotid gland usually results in better function, even for relatively low mean doses (<1000 cGy).”3 The same review examining larynx and pharynx dose–volume effects had a similar conclusion stating that planners should minimize the volume of pharyngeal constrictors and larynx receiving 6000 cGy, and when, possible 5000 cGy 6. Both publications emphasize the concept of minimizing the dose to these structures beyond the published/accepted benchmarks (i.e., as low as achievable).…”
Section: Introductionmentioning
confidence: 99%